Efficacy and safety of anthelmintics tested against Taenia solium cysticercosis in pigs. - Ernatus Martin Mkupasi; Chummy Sikalizyo Sikasunge; Helena Aminiel Ngowi; Maria Vang Johansen (Public Library of Science (PLoS), 2013)
Porcine cysticercosis, an infection caused by Taenia solium metacestodes, is continuously being reported in low-income countries of Latin America, Asia, and sub-Saharan Africa. The disease was declared eradicable by the International Task Force for Diseases Eradication (ITFDE) in 1993, and it is listed among the 17 WHO Neglected Tropical Diseases and Neglected Zoonoses that are potentially eradicable. In view of that, WHO has proposed a step-wise approach to its elimination, including chemotherapy of infected pigs. Different drugs have been tested on porcine cysticercosis with varying efficacies. These include flubendazole, fenbendazole, albendazole, albendazole sulphoxide, oxfendazole, praziquantel, and nitazoxanide. This review summarises available information on the efficacies and adverse effects shown by these drugs in pigs. Oxfendazole has shown to be effective for the control of porcine cysticercosis; however, it needs to be integrated with other control approaches. There is a need for standardised guidelines for evaluating the efficacy of anthelmintics against porcine cysticercosis, and more efficacy studies are needed since the conclusions so far are based on a limited number of studies using few infected pigs.